Light-promoted metal-free cross dehydrogenative couplings on ethers mediated by NFSI: reactivity and mechanistic studies. Issue 94 (15th November 2017) - Beniazza, Redouane; Abadie, Baptiste; Remisse, Lionel; Jardel, Damien; Lastécouères, Dominique; Vincent, Jean-Marc
Abstract : Cross dehydrogenative couplings on ethers are performed very effectively in a one-pot process using NFSI as oxidizing agent under low-intensity UVA irradiation in the presence of 2 mol% benzophenone. Abstract : Cross dehydrogenative couplings on ethers occur very effectively using N -fluorobis(phenyl)sulfonimide (NFSI) as oxidizing agent under UVA irradiation in the presence of 2 mol% benzophenone. The reaction was shown to proceed first by fast radical fluorination of the α-C–H bond of ethers, followed by HF elimination to yield the highly electrophilic oxocarbenium ion as a key intermediate.